OPTIMIZATION OF FERMENTATIVE CONDITIONS OF Pichia membranifaciens FOR SECOND GENERATION ETANOL PRODUCTION - Ribeiro, Natalia N. [UNESP]; Freita, Lidyane A. [UNESP]; Tralli, Leticia F. [UNESP]; Silva, Aline F. [UNESP]; Freita, Cristhyane M. [UNESP]; Mendes, Franciele Q. [UNESP]; Teixeira, Vitor [UNESP]; Junior, Calisto N. S. [UNESP]; Mutton, Marcia J. R. [UNESP] (Soc Brasileira Quimica, 2019)
Technologies developed in the last decade have made viable the use of lignocellulosic materials for the production of ethanol. However, to improve the fermentative yield some improvements are necessary, among them the search for new microorganisms capable of fermenting sugars with five carbons. Thus, the present research aimed to determine the best pH and temperature for Pichia membranifaciens LJ04 in synthetic medium containing pentose, aiming at the biotechnological production of ethanol from hemicellulosic hydrolysate. The experimental design was completely randomized in Split-Split-Plot, with 3 replicates. The main treatments were pHs (3.5, 4.0 and 4.5), the secondary were temperatures (32 degrees C, 37 degrees C and 40 degrees C) and the tertiary were fermentation periods (0, 6, 12 and 24 hours). It was determined in this study that the ideal conditions were temperature of 32 degrees C and pH 4.0-4.5. With these conditions there was higher xylose consumption, high ethanol production, low production of secondary compounds and high rates of cell viability during fermentation.
Keywords: ethanolic fermentation; temperature; pH; synthetic hydrolysate; pentose